Mechanical and thermal properties of chitosan filled recycled polyethylene biocomposites - Azieyanti Nurain Azmin (School of Materials Engineering, 2010)
The research is emphasized the utilization of chitosan as biopolymer in recycled polyethylene (RPE) biocomposites on properties. The objectives of study include: 1) to determine the effect of chitosan loading on mechanical properties, thermal properties, water absorption and morphology of recycled polyethylene biocomposites; 2) to investigate the effect of coupling agent, compatibilizer and both on properties of RPE/chitosan biocomposites; 3) to assess the effect of eco-degradant on properties of RPE/chitosan biocomposites.